Evaluating the O‐Cr‐Mo isotope signatures in various meteorites representing core–mantle–crust fragments: Implications for partially differentiated planetesimal(s) accreted in the early outer solar system. (7th February 2021) - Ali, Arshad; Jabeen, Iffat
Abstract: The Allende, Eagle Station pallasites (ESP), some ungrouped achondrites (UA), and ungrouped irons (UI) represent different types of meteorites; these are traditionally distinguished as chondrule‐bearing chondrite, chondrule‐free stony irons, stones, and irons, respectively. Oxygen isotopic compositions of meteorites have long been used as a robust tool to identify the parent bodies of these extraterrestrial materials. We revisited the δ 18 O‐∆ 17 O, along with ε 54 Cr and ε 92 Mo, of these meteorites and established a genetic link that possibly suggests that undifferentiated carbonaceous chondrites and their differentiated counterparts belong to a common reservoir. We observed that the differentiated counterparts of Allende CV3 including ESP, ungrouped achondrites, and ungrouped irons collectively provide the oxygen isotope trends comparable to those of the Y&R and the PCM lines, and are likely to represent the primitive isotope reservoirs in the solar nebula. ε 54 Cr and ε 92 Mo data of these meteorite types support their oxygen isotope trends. The idea of a common partially differentiated parent body also lends support from natural remnant magnetization in the CV chondrites and Eagle Station olivine. Furthermore, ∆ 17 O‐ε 54 Cr data suggest that these meteorites originated from carbonaceous planetesimal(s) accreted at different heliocentric distances in the solar nebula in the outer solar system. As proposed earlier, these bodies remained separated from the inner solar system due to formation of Jupiter. Taken together, we propose that the ungrouped irons, ESP, and ungrouped achondrites could possibly represent the differentiated sections, such as core, core–mantle, and mantle of a planetesimal(s), respectively, with the Allende CV3 representing an undifferentiated chondritic crust.